The Influence of Environmental Awareness and Attitudes towards the Environment on Achieving SDGs Through Green Entrepreneurship Behavior as a Mediating Variable - Ali, Mukti; Aziza, Nurul; Budi Hartanto, Nur Rahmat (Jurnal Bisnis dan Kewirausahaan, 2025)
This study is motivated by the urgency of achieving the Sustainable Development Goals (SDGs), which require the active participation of the younger generation, especially students, as agents of sustainable change. Low environmental literacy and green entrepreneurship behavior pose challenges in encouraging student contributions to SDG implementation. Therefore, this study aims to analyze the influence of environmental knowledge and attitudes toward the environment on support for SDG achievement, with green entrepreneurship behavior as a mediating variable. This study uses a quantitative method with a Partial Least Square (PLS) approach through the SmartPLS 4.0 application. Data were obtained through an online questionnaire distributed to 274 students at Maarif Hasyim Latif University, after the research instrument was tested for validity and reliability using SPSS version 31 with highly reliable results (Cronbach Alpha 0.944). The R-square value for the green entrepreneurship behavior variable was 0.482 (moderate category) and for the support for SDGs variable was 0.673 (strong category). The results showed that environmental knowledge had a significant effect on green entrepreneurship behavior and support for achieving SDGs, while attitudes toward the environment did not have a significant effect on either variable. Furthermore, green entrepreneurship behavior proved to be a strong and significant mediating variable in increasing support for SDGs. These findings emphasize the importance of strengthening environmental literacy and fostering green entrepreneurship in higher education to encourage student’s role in realizing sustainable development.